Discricionariedade administrativa e "discricionariedade técnica" - Nardi, Luciana Sant'Ana (2009)
The aim of this study is to understand the so-called technical discretion , its meaning, its scope and whether it features the legal regime present in the administrative discretion. At first the expression technical discretion started to be used in order to avoid legal control over some administrative actions. Since then it has been used in several different meanings, which has resulted in great doctrinal and jurisprudential divergence. Firstly on this paper, we started with a research about the concept and the normative structure of the administrative discretion. Such research includes an analysis of its basis and its relation with legal principles. On this project, we intend to cover the legal system involved in the administrative discretion, so that we may analyse whether the so called technical discretion exists and if a different legal system is applied in this case. Secondly, we present an analysis of the so called technical discretion , including studies of its origin, its evolution on the Spanish, Italian and North American doctrines and the opinion of the Brazilian doctrine on this matter. Our researches gave emphasis to the activities of regulatory agencies since the concept of technical discretion has been used by them to support such activities and these procedures may, consequently, cause the breach of legal principles. Finally, a discussion on the judicial control over administration is also presented, since such procedure ensures that administrative activities are followed in accordance with the orders set forth in the legislation and, for this reason, as a consequence, a clash between freedom of administration and judicial control authority arises. Such controversial question is considered of greatest importance for the Administrative Law. Taking the aforementioned facts into consideration, we prepared a research about the principles of Public Administration and the theories explaining why objectives are conducted to different directions